2012
DOI: 10.2337/dc11-2281
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality Over 8 Years in Type 2 Diabetic Patients

Abstract: OBJECTIVETo examine demographic, socioeconomic, and biological risk factors for all-cause, cardiovascular, and noncardiovascular mortality in patients with type 2 diabetes over 8 years and to construct mortality prediction equations.RESEARCH DESIGN AND METHODSBeginning in 2000, survey and medical record information was obtained from 8,334 participants in Translating Research Into Action for Diabetes (TRIAD), a multicenter prospective observational study of diabetes care in managed care. The National Death Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 12 publications
4
94
1
1
Order By: Relevance
“…1). Following detailed assessments, and after the inclusion of three articles identified from manual searches, 21 articles were included in the quantitative analysis (21 studies and 24 unique cohorts; Table 1) [7,8,11,15,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Study characteristics and the NOS scores are provided in ESM Tables 1-3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Following detailed assessments, and after the inclusion of three articles identified from manual searches, 21 articles were included in the quantitative analysis (21 studies and 24 unique cohorts; Table 1) [7,8,11,15,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Study characteristics and the NOS scores are provided in ESM Tables 1-3.…”
Section: Resultsmentioning
confidence: 99%
“…However, evidence on the association between obesity and mortality in patients with diabetes remains inconclusive with some studies reporting an inverse association between obesity (estimated using the conventional Electronic supplementary material The online version of this article (doi:10.1007/s00125-016-4162-6) contains peer-reviewed but unedited supplementary material, which is available to authorised users. measure of BMI) and mortality [4][5][6], some reporting U-shaped associations [7,8], some reporting linear positive associations [9,10], and some reporting no association [11].…”
Section: Introductionmentioning
confidence: 99%
“…15 Because of the high morbidity, mortality, and cost associated with T2DM, there is a need to develop models to simulate the long-term outcomes and costs of T2DM beyond the time horizon of clinical trials. Because CVD is the leading cause of morbidity and mortality in people with T2DM, 16,17 it is important that any computer model for T2DM incorporate a valid submodel for CHD. Unless that model simulates medication effects and surgical practices explicitly, it will not accurately predict the CVD outcomes observed in clinical studies.…”
mentioning
confidence: 99%
“…Most previous studies did not exclude patients with a history of CVD and cancer when they assessed the association between BMI and the risk of mortality among individuals with type 2 diabetes. [4][5][6] The analysis by Jackson et al 7 excluded individuals who reported a prior history of cancer and/or coronary heart disease, which can minimize the influence of reverse causation.…”
mentioning
confidence: 99%
“…3,5,7 However, many previous studies had small samples, and thus lacked adequate statistical power when the analysis was limited to those who have never smoked. 4,6 The third methodological concern in some analyses between body weight and mortality is that the physiologic effects of excess fatness, such as hypertension, diabetes, and dyslipidemia, were controlled statistically, thus artificially removing some of the effects of being overweight. Most of the studies assessing the association of BMI and morality risk among individuals with type 2 diabetes have taken this potential over-adjustment for weight-related risk factors into consideration.…”
mentioning
confidence: 99%